Heterosexual Missionary as the Sexual Default and Stigmatization of Perceived Infrequent Sexual Activities - Reysen, Stephen; Shaw, Jennifer; Brooks, Thomas R. (Advances in Social Sciences Research Journal, 2015)
In the present study we examined whether heterosexual vaginal intercourse is the default prototype of sex and the association between the perceived frequency of sexual activities and prejudice toward individuals who engage in those activities. Participants rated 132 sexual activities and preferences with respect to perceived frequency that others engage in those activities and prejudice toward others who engage in the activities. The results suggested that heterosexual vaginal intercourse (missionary) is the default prototype of sex. Furthermore, the results showed a strong association between the perceived infrequency of sexual activities and prejudice toward individuals who engage in them. Together, the results suggested that the perceived norms of sexual behaviors contribute to the perceptions of other individuals and groups.